Percy Jackson and the last olympian - Rick Riordan (UK Puffin, 2018)
Percy Jackson and the Last Olympian is the fifth novel in Rick Riordan$1 (Bs bestselling fantasy fiction series, Percy Jackson and the Olympians. Kronos, the Lord of Time, has escaped his prison in Tartarus. Now he makes his way towards New York City, and the only ones who have any chance of stopping the mighty Titan are the Olympians, who are busy with the rampaging monster Typhon. Percy Jackson, the son of Poseidon, tries to fight off Kronos with Beckendorf, the son of Hephaestus. However, Kronos is too powerful even for them. Percy needs to understand the truth about his past and his duty towards mankind to be able to stand any chance against the might Titan. Gods, Demi-Gods and all manner of creatures out of ancient mythology come alive on the streets of Manhatten for a battle to end all battles. The fate of Western Civilization itself hangs in the balance. In this final book in the Percy Jackson and the Olympians series, Percy will have to embrace his fate, and understand what prophecy has laid in store for him since before he was even borns
Keywords: American Fiction